Adsorption isotherms and heat of sorption of fresh and preosmosed oven-dried bananas (2005)
"Three banana varieties (Omini Red, Cavendish and Cooking banana) were transversely cut into 10 mm slices, pretreated in sucrose solution of 52, 60 and 68°B and maintained at 25°C for 12 hours. Both fresh and preosmosed banana slices were subsequently oven-dried at 60°C for 72 hours. Adsorption isotherms of fresh and preosmosed oven-dried banana slices were determined at 20 and 40°C using gravimetric–static method. Suitability of eight sorption models in describing the adsorption data was tested. Moreover, isosteric heat of sorption of both fresh and preosmosed oven-dried bananas was determined using Clausius–Clapeyron equation. Adsorption isotherms of fresh and preosmosed oven-dried banana slices gave type I (J–shaped) isotherms. Isotherms were affected by temperature and pretreatment sucrose solution concentration. Crossing of isotherms occurred at aw~0.55-0.70. Among the eight models, tested, Guggenheim-Anderson-de Boer (GAB) model gave the best fit. Calculated GAB monolayer moisture (Mm) content (9.80–20.8% d.b.) decreased with increase in temperature. Generally GAB Mm content increased with increase in total solids (%) content of preosmosed banana slices. Isosteric heat of sorption increased with decreased moisture content in banana slices. "